2011
DOI: 10.1158/0008-5472.can-10-1704
|View full text |Cite
|
Sign up to set email alerts
|

Nm23-H1 Indirectly Promotes the Survival of Acute Myeloid Leukemia Blast Cells by Binding to More Mature Components of the Leukemic Clone

Abstract: Nm23-H1 plays complex roles in the development of diverse cancers including breast carcinoma, high-grade lymphomas, and acute myeloid leukemia (AML). In the case of AML and lymphomas, serum Nm23-H1 protein is elevated with the highest levels correlating with poorest prognosis. A recent study identified that this association is most likely causal in AML and that Nm23-H1 acts as an AML cell survival factor. In this study, we report heterogeneity in the ability of AML samples to bind and respond to Nm23-H1, and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Moreover, NM23-H1 functions are not always intracellular, judging from activities mediated by extracellular NM23 (34,35). In particular, the protein is overexpressed in some tumors, including hematologic malignancies, and is present at elevated levels in patient sera, where the protein seems to promote tumor cell growth and survival by autocrine and/or paracrine mechanisms (36)(37)(38)(39). In the present study, we show that NM23-H1 lacking an MTD sequence does not efficiently enter cells.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, NM23-H1 functions are not always intracellular, judging from activities mediated by extracellular NM23 (34,35). In particular, the protein is overexpressed in some tumors, including hematologic malignancies, and is present at elevated levels in patient sera, where the protein seems to promote tumor cell growth and survival by autocrine and/or paracrine mechanisms (36)(37)(38)(39). In the present study, we show that NM23-H1 lacking an MTD sequence does not efficiently enter cells.…”
Section: Discussionmentioning
confidence: 75%
“…The gene is highly conserved from yeast to humans, implying a critical developmental function. Cell surface nm23-H1 has been previously observed in non-Hodgkin lymphoma (NHL) cells (12,13) and certain myeloid cell lines (14,15). Specific studies (13,14) have demonstrated that tumors with a reduced expression of the nm23 gene are more prone to metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Cell surface nm23-H1 has been previously observed in non-Hodgkin lymphoma (NHL) cells (12,13) and certain myeloid cell lines (14,15). Specific studies (13,14) have demonstrated that tumors with a reduced expression of the nm23 gene are more prone to metastasis. It has been also previously documented that the expression of nm23-H1 transcripts and, more so, the levels of nm23-H1 protein in serum, provide strong indicators of prognosis, with higher values being associated with poorer overall survival (1315).…”
Section: Discussionmentioning
confidence: 98%
“…However, Bircan et al (Bircan et al, 2008) reported that the increased NME1 expression was of no prognostic value in a series of Hodgkin and non Hodgkin lymphoma. Pointing to a role of extracellular NME1, recombinant NME1 protein was shown to promote the survival of acute myeloid leukemia blast cells (Okabe-Kado et al, 2009a;Lilly et al, 2011) but to decrease the survival of primary cultured normal peripheral blood mononuclear cells (Okabe-Kado et al, 2009b).…”
Section: Notementioning
confidence: 99%